Clinical Strains of Helicobacter pylori With Strong Cell Invasiveness and the Protective Effect of Patchouli Alcohol by Improving miR-30b/C Mediated Xenophagy - Xu, Yifei; Deng, Qiuhua; Zhong, Yuanzun; Jing, Li; Li, Haiwen; Li, Jingwei; Yu, Huimin; Pan, Huafeng; Guo, Shaoju; Cao, Hongying; Huang, Ping; Huang, Bin (Frontiers in Pharmacology, 2021)
Helicobacter pylori was classified by the World Health Organization as a class 1 carcinogen. The development of drug-resistant strains of this pathogen poses a serious threat to human health worldwide. The cell invasion of H. pylori activates xenophagy in gastric epithelial cells by mediating miR-30b/c, and the emergence of autophagosomes provides a niche that enables the survival of intracellular H. pylori and promotes its drug resistance. This study revealed that some clinical drug-resistant H. pylori strains present much stronger invasive ability than standard strains. Patchouli alcohol (PA), a tricyclic sesquiterpene from Pogostemon cablin (Blanco) Benth (Labiatae), showed reliable activity against intracellular H. pylori. The mechanisms appeared to involve the downregulation of miR-30c-3p/5p and miR-30b-5p, thereby upregulating xenophagy-related gene expression (ULK1, ATG5, ATG12, and ATG14) and enhancing xenophagy. PA also inhibited the nuclear transfection of miR-30b-5p induced by H. pylori, thereby enhancing transcription factor EB function and increasing lysosome activity. The finding of strongly invasive intracellular H. pylori has great implications for clinical treatment, and PA can act against invasive H. pylori based on the improvement of miR-30b/c mediated xenophagy. Taken together, the results demonstrate that PA have potential use as a candidate medication for intracellular drug-resistant H. pylori.